Pengakuan dan Legitimitas di Hukum Internasional: Studi Kasus Konflik Israel-Palestina - Yuni Putri Dewantara; Michelle Hadi; Carissa Amanda Siswanto (Jurnal Hukum Lex Generalis, 2025)
The conflict between Israel and Palestine is receiving a lot of attention from the world community. This calls into doubt the security of every nation, particularly those engaged in hostilities. In order to better understand how Israel's military aggression against Palestine breaches international humanitarian law, this case study will focus on how the UN is in charge of deciding whether or not Palestine is recognized by international law. This study analyzes legal concerns using a normative juridical method. The criteria and tenets of positive law serve as the foundation for this. The concept of the law of war is the foundation of international humanitarian law, which governs armed conflicts in an effort to prevent atrocities and safeguard all parties.